2011
DOI: 10.1007/s11255-011-9917-x
|View full text |Cite
|
Sign up to set email alerts
|

Association between depression and malnutrition–inflammation complex syndrome in patients with continuous ambulatory peritoneal dialysis

Abstract: Depression is commonly encountered in Chinese CAPD patients. A close relationship exists between depression and MICS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 35 publications
0
35
0
Order By: Relevance
“…28 In another study using The Hamilton Depression Scale (HAMD), serum CRP closely correlated with depression score in CAPD patients. 29 However, other studies could not demonstrate such a relationship between CRP and inflammation. [30][31][32] Using different cutoff points for screening and diagnosis of depression symptoms by assessment tools may be a possible reason for the contradictory results of different studies.…”
Section: Discussionmentioning
confidence: 95%
“…28 In another study using The Hamilton Depression Scale (HAMD), serum CRP closely correlated with depression score in CAPD patients. 29 However, other studies could not demonstrate such a relationship between CRP and inflammation. [30][31][32] Using different cutoff points for screening and diagnosis of depression symptoms by assessment tools may be a possible reason for the contradictory results of different studies.…”
Section: Discussionmentioning
confidence: 95%
“…These malnourished patients had lower albumin and higher CRP levels as expected. It is well known that malnutrition in dialysis patients is closely associated with chronic inflammation as a part of malnutrition-inflammationatherosclerosis syndrome (MIA) and at the end, is one of the and the malnutrition-inflammation score was independent risk factor for depression in peritoneal dialysis patients (27). Similarly Micozkadioglu et al reported an association between depressive findings and malnutrition-inflammation complex in hemodialysis patients (28).…”
Section: Türk Nefroloji Diyaliz Ve Transplantasyon Dergisi Turkish Nementioning
confidence: 98%
“…Recently, many authors try to investigate the connection between depression and inflammatory status in ESRD patients. 31 Meanwhile, the disorder of ApoE may be influenced by inflammatory cytokines in the dialysis population, though there is no difference in hsCRP between the two groups. 32 A few limitations in the current study should be noted.…”
Section: Patient Groupmentioning
confidence: 99%